IMPLEMENTATION OF INTERACTIVE FOLKTALE VIDEO ON TOEFL PROBLEM-SOLVING ABILITY - Liansari, Vevy; Ermawati Zulikhatin Nuroh; Rahmania Sri Untari; Nuril Lutvi (Antis-publisher, 2025)
Objective: This study aims to address the challenges faced by Communication Science students at Universitas Muhammadiyah Sidoarjo (Umsida) in mastering the Test of English as a Foreign Language (TOEFL) by implementing an innovative learning medium, the interactive folktale video. Method: The program employed a structured approach consisting of initial observation, needs assessment, instructional design, implementation of training sessions, and post-intervention evaluation. Results: The findings indicate a significant improvement in students' TOEFL performance, particularly in the areas of listening comprehension, structure and written expression, and reading comprehension, following the integration of interactive folktale videos into their learning process. Novelty: The originality of this study lies in its unique combination of cultural narratives with interactive multimedia technology to enhance English language proficiency, providing a culturally relevant and engaging approach to TOEFL preparation rarely explored in existing literature.